PEMBERDAYAAN INKLUSIF BERBASIS KOMUNITAS: DINAMIKA KONTEKS IMPLEMENTASI PROGRAM SEKOLAH PEREMPUAN SRIKANDI DI KOTA DENPASAR - Putra, I Putu Adi Permana; Novitasari, I Gusti Ayu Ngurah Valencia; Sumawidayani, Nyoman (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2026)
The Srikandi Women's School (Sekolah Perempuan Srikandi) program serves as an affirmative policy intervention to address gender inequality. Previously, vulnerable women in the village confronted hierarchical institutional structures, a deeply entrenched patriarchal culture that fostered apathy, low public participation, and susceptibility to domestic issues. This study aims to analyze the implementation dynamics of the program employing Merilee S. Grindle's (1980) policy implementation model. A descriptive qualitative approach was utilized for this research. Data were collected through observations, in-depth interviews, and document analysis. Primary data were gathered extensively from village officials, facilitators of the Bali Sruti Foundation, and program participants. Regarding the Content of Policy dimension, the findings reveal an asymmetry of empowerment; while the program has been massively successful in distributing non-material benefits such as critical awareness, enhanced self-confidence, and social agency it remains on a micro-scale concerning the provision of structural financial autonomy. Strategic decision-making remains mediated by the village bureaucratic elites. Within the Context of Implementation dimension, the village's political ecology demonstrates progressive political will, evidenced by the program's institutionalization into the Village Revenue and Expenditure Budget (APBDes). The andragogical mentoring strategy has proven effective in fostering intrinsic compliance and consistent responsiveness among participants. However, the program is still largely perceived as a socio-educational activity, not yet addressing power-sharing and patriarchal domestic relations. In conclusion, this study indicates that the Women's School Program serves as an effective incubator for social agency, successfully dismantling women's apathy. Nevertheless, enhancing economic access and decentralizing political authority are essential to realize sustainable gender equality.